2020
DOI: 10.1093/nutrit/nuz071
|View full text |Cite
|
Sign up to set email alerts
|

Effect of quercetin supplementation on plasma lipid profiles, blood pressure, and glucose levels: a systematic review and meta-analysis

Abstract: Context Clinical trials examining the cardiovascular protective effects of quercetin in humans have reported conflicting results. Objective The aim of this systematic review was to summarize evidence of the effects of quercetin supplementation on plasma lipid profiles, blood pressure (BP), and glucose levels in humans by performing a meta-analysis of randomized controlled trials. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 44 publications
3
54
0
1
Order By: Relevance
“…Altogether, these results indicate a significant anti-hypertensive effect of quercetin supplementation only when doses ≥500 mg/day are taken for ≥8weeks (137). Another meta-analysis which included 896 participants across 17 RCTS mirrored the results obtained by Serban et al, which indeed is the meta-analysis done by Huang et al (138). More recently, a meta-analysis of 8 RCTs conducted among patients with metabolic syndrome traits showed that quercetin supplementation significantly reduced systolic BP, yet did not affect diastolic BP (139).…”
Section: Vasodilating Effects Of Quercetinsupporting
confidence: 52%
“…Altogether, these results indicate a significant anti-hypertensive effect of quercetin supplementation only when doses ≥500 mg/day are taken for ≥8weeks (137). Another meta-analysis which included 896 participants across 17 RCTS mirrored the results obtained by Serban et al, which indeed is the meta-analysis done by Huang et al (138). More recently, a meta-analysis of 8 RCTs conducted among patients with metabolic syndrome traits showed that quercetin supplementation significantly reduced systolic BP, yet did not affect diastolic BP (139).…”
Section: Vasodilating Effects Of Quercetinsupporting
confidence: 52%
“…Other studies have shown the effectiveness of QC in minimizing dyslipidemia. 40,41 Furthermore, DOX treatment increased the atherogenic index and this was decreased by the combination therapy. Sitagliptin in previous studies has proven to have anti-atherosclerotic activity related to its ability to decrease lipid accumulation, in addition to the antioxidant and anti-inflammatory activities that aid in inhibiting the progress of atherosclerosis.…”
Section: Discussionmentioning
confidence: 98%
“…A recent systematic review and meta-analysis on the effect of quercetin against cardiovascular diseases demonstrated that long-term supplementation with quercetin could lower blood pressure, high-density lipoprotein cholesterol, and triglycerides in humans [ 26 ]. In addition, it is very meaningful that our study showed that quercetin supplementation could prevent even sudden cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%